Deterministic and Stochastic Seismic Inversion techniques towards a better prediction for the reservoir distribution in NEAG-2 Field, north Western Desert, Egypt - O. Rashad; A.N. El-Barkooky; A. El-Araby; M. El-Tonbary (Egyptian Journal of Petroleum)
NEAG 2 field is one of the key economic oil fields in the company that was contributing to 35% of total liquid production in 2016. Despite that, the full field potentiality is still not estimated precisely. The field lies within the Northeast part of Abu El-Gharadig (NEAG Extension concession). Albian-Cenomanian Kharita-Bahariya is the targeted reservoir section. The reservoir distribution trends are not clear and cannot be predicted easily. Thus, the main uncertainty is to trace the reservoir extension. Since inversions of seismic into absolute impedance rely on well data for their parameterization, they are typically conducted in brownfields like NEAG 2. In addition, the reservoir quality and thickness in NEAG 2 encouraged the application of the seismic inversion approach, to gain a large-scale insight into the reservoir distribution qualitatively and quantitatively, if possible. Also, to mitigate the reservoir trends uncertainty, and assess its spatial continuity in the uncalibrated areas. There were some concerns about the seismic quality, although, several trials were implemented to get the best results and overcome the seismic vagueness. The post-stack seismic inversion workflow was applied in Hampson-Russel Software Suite. A Deterministic approach was followed by a Stochastic approach in an adopted workflow. The workflow was accomplished by generating several Stochastic Impedance realizations. To cover the uncertainty range, P10, P50 and, P90 realizations were generated and analyzed. Additionally, a connectivity analysis was done, to compute the probability of communication between the wells. The inverted volume helped to distinguish between different reservoir bodies' geometries and dimensions, which cannot be revealed from the conventional seismic interpretation. The reservoir bodies were resolved and quantified as channels and bars. Followed by the Stochastic workflow which produced multiple realizations, allowing the seismic uncertainty to be assessed. This research work will be the first of its kind for the Kharita-Bahariya section in NE Abu-Gharadig Basin.